Assessing Children's Credibility in Courtroom Investigations of Alleged Child Sexual Abuse: Suggestibility, Plausibility, and Consistency. (May 2020) - Denne, Emily; Sullivan, Colleen; Ernest, Kyle; Stolzenberg, Stacia N.
As children's testimonies of child sexual abuse (CSA) often lack concrete evidence to corroborate a child's claims, attorneys devote a substantial amount of time to establishing a child as credible during the course of a trial. Examining 134 CSA victim testimonies for children aged 5–17 ( M = 12.48, SD = 3.34; 90% female), we explored how attorneys assess child credibility through specifically targeting children's suggestibility/honesty, plausibility, and consistency. Results revealed that while prosecutors examine plausibility more often to establish credibility, defense attorneys focus their assessments on suggestibility/honesty and potential inconsistency. However, both attorneys asked many more questions about children's consistency than any other area of potential credibility. Furthermore, while prosecutors ask proportionally more credibility-challenging questions of older children, the defense do not. These results suggest that prosecutors may be missing an opportunity to establish children as honest and consistent and elucidate a need to train attorneys on the implications of children's inconsistencies, suggestibility, and plausible abuse dynamics.